La superación de la metafísica de la subjetividad a través de una analítica de la coexistencia - Salerno, Gustavo (2020)
“Overcoming the metaphysics of subjectivity through an analytic of coexistence”. In this article, I operationally characterize Heidegger’s early thinking as a “philosophy of intersubjectivity”. This will allow me to make a contrast of his contribution to what he defines as “metaphysics of subjectivity”: it is a philo-sophical horizon that Heidegger criticizes, and that I will reconstruct paying special attention to the phenomenology of Husserl. It is possible to make this comparison by circumscribing the ontological program of Being and Time to the terms of the preparatory study preceding the question of being, and of the understanding of it as an analytic of coexistence.